2009
DOI: 10.1111/j.1468-2389.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Beauty Revisited: The impact of attractiveness, ability, and personality in the assessment of employment suitability

Abstract: This study examined the relative weight that hiring managers place on applicants' attractiveness, general mental ability (GMA), and the Big Five personality dimensions in assessing employment suitability for high and low customer contact positions. A sample of 130 managers from 43 hotel properties in the United States and Canada evaluated applicant profiles that varied on these dimensions. The policy capturing results demonstrated that attractiveness does impact employment suitability ratings across positions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 53 publications
4
81
0
1
Order By: Relevance
“…One study on hiring recommendations (Tews, Stafford, & Zhu, 2009) included information on general mental ability, the five-factor personality variables, and facial photographs. The authors found that attractiveness influenced hiring decisions over and above ability and conscientiousness, particularly for high customer contact jobs (see also Freng & Webber, 2009).…”
Section: Other Social Media Processes/individual Differences That Coumentioning
confidence: 99%
“…One study on hiring recommendations (Tews, Stafford, & Zhu, 2009) included information on general mental ability, the five-factor personality variables, and facial photographs. The authors found that attractiveness influenced hiring decisions over and above ability and conscientiousness, particularly for high customer contact jobs (see also Freng & Webber, 2009).…”
Section: Other Social Media Processes/individual Differences That Coumentioning
confidence: 99%
“…However, most of these investigations have analysed beauty as a motivation for remuneration (Andreoni & Petrie, 2008;Benzeval, Green & Macintyre, 2013;French, 2002;Hamermesh & Biddle, 1993;Mobius & Rosenblat, 2006;Robins, Homer & French, 2011;Tews, Stafford & Zhu, 2009). This research would focus on hiring decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Managers may use physical attractiveness to make generalised inferences about a candidate regarding employment suitability as it is an easily identifiable characteristic (Tews et al, 2009). In a related study, 50% of employers who had recently hired candidates to fill a position answered that physical appearance was very important (11%) or somewhat important (39%) (Holzer, 1993).…”
Section: Beauty and The Beauty Premiummentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of physical attractiveness has also been studied in other areas of research, such as the impact of beauty in the labor-market (e.g., Hamermesh & Biddle, 1993) or employment suitability (e.g., Tews, Stafford, & Zhu, 2009).…”
Section: Introductionmentioning
confidence: 99%